The Relationship Between Entrepreneurship, Entrepreneur Background, and Future Market Anticipation - Rodhiah Rodhiah; Nur Hidayah (International Journal of Management Science and Application, 2025)
The rapid and competitive development of entrepreneurship demands that entrepreneurs become more creative and innovative in creating or designing their products and services to meet the increasingly diverse needs of society. To enhance the entrepreneurial spirit in business, market anticipation for the future is necessary so that the products produced can compete with other competitors and generate profits. The purpose of this research is to understand the relationship between entrepreneurship, the background of entrepreneurs, and future market anticipation. This research uses a sample, employing a purposive sampling technique. Data were collected through the distribution of questionnaires to respondents located in Tangerang who are members of the sample. This data analysis technique uses SEM with Smart PLS. The research results show entrepreneurship has a positive and significant impact on future market anticipation. Entrepreneurial background has a positive and significant impact on future market anticipation. Entrepreneurial background has an insignificant impact on entrepreneurship.